2020
DOI: 10.3390/su12062243
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth, Public and Private Investment: A Comparative Study of China and the United States

Abstract: Public and private investments play a central role in production functions by providing the required capital for development. There are many studies in the literature investigating the linear macroeconomic relations based on public and private investment in cross-country and country-specific analyses by focusing on various perspectives and methodologies. However, there is a gap in the literature in exploring nonlinear causal relations among public-private investment and economic growth, particularly in the U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The Foundation, which has been operating in the territory of Ukraine since 1994, acts as a sponsor of students and a significant partner in Ukraine's political and economic transformation (Konrad Adenauer Foundation, 2020). (Soreg & Bermudez-Gonzalez, 2021;Ari & Koc, 2020;Boudreaux, Nikolaev & Klein, 2019;Qureshi et al, 2019;Chaudhry, Xu & Cao, 2018), taking into account the relevance of the scope ICC, DOBRE, U-LEAD programs, funds from the Konrad Adenauer Foundation. Thus, within the study, a pool of 21 indicators (Table 1) was formed which characterize the socio-economic development of the country, and indicators reflecting the impact on it of funds attracted from foreign NGOs (Table 1): U-LEAD -amount of funding under the U-LEAD program, million euros Y1-Y4), and determined using a linguistic, numerical scale (Gorelova, Pankratova & Borisova, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The Foundation, which has been operating in the territory of Ukraine since 1994, acts as a sponsor of students and a significant partner in Ukraine's political and economic transformation (Konrad Adenauer Foundation, 2020). (Soreg & Bermudez-Gonzalez, 2021;Ari & Koc, 2020;Boudreaux, Nikolaev & Klein, 2019;Qureshi et al, 2019;Chaudhry, Xu & Cao, 2018), taking into account the relevance of the scope ICC, DOBRE, U-LEAD programs, funds from the Konrad Adenauer Foundation. Thus, within the study, a pool of 21 indicators (Table 1) was formed which characterize the socio-economic development of the country, and indicators reflecting the impact on it of funds attracted from foreign NGOs (Table 1): U-LEAD -amount of funding under the U-LEAD program, million euros Y1-Y4), and determined using a linguistic, numerical scale (Gorelova, Pankratova & Borisova, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The first stage of the study was the formation of indicators characterizing the effectiveness of the fiscal policy, based on the IMF methodology for assessing fiscal risks (International Monetary Fund, 2016), as well as scientific publications (Makin & Layton, 2021;Hu & Lei, 2017;Bouakez, Guillard & Roulleau-Pasdeloup, 2020) and indicators of macroeconomic development in Azerbaijan (Ari & Koc, 2020;Soreg & Bermudez-Gonzalez, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Domestic credit to the private sector is broadly employed as a proxy for financial development in the literature. To the best of our knowledge, Schumpeter (1912) proposed for the first time that domestic credit in the banking sector finances investments [31], which is divided into public and private investments that should stimulate each other for sustainable economic development [32]. Several empirical studies, such as that by King and Levine (1993) [33], found evidence that an increase in financial service performance leads to real economic growth.…”
Section: Datamentioning
confidence: 99%